Perbandingan Daya Hambat Bakteri Pseudomonas Fluorescens Asal Tomat, Kedelai, dan Jagung Terhadap Ralstonia Solanacearum Secara In Vitro - Aco Roni Kirihio; Ivonne F. Mariay; Cipta Meliala (Fakultas Pertanian Universitas Papua, 2017)
Inhibition of P. fluorescens isolates the origin of tomato, soybean and corn against R. solanacearum tested using a completely randomized design (CRD). P. fluorescens growth was measured at King's B medium by way of suspension antagonist put on filter paper of 0.5 cm in diameter. Inhibition of P. fluorescens is done by placing the antagonist suspension of 0.5 cm diameter filter paper on NA media that has been deployed R. solanacearum. The results showed that: (a) the growth of P. fluorescens origin of tomato, soybean and corn on King's B media were not significantly different, (b) the inhibition of P. fluorescens isolates against R. solanacearum not significantly different and, (c) the inhibition of isolates P. fluorescens origin of tomato, soybean and corn against R. solanacearum in vitro relatively strong.